Corporate Legal Dogmatics on the Revocation of Share Donation Due to Breach of the Duty of Loyalty - Burduli Irakli; Chitashvili Natia (TalTech Journal of European Studies)
The article is devoted to the research of the institution of revocation of share donation and, mainly based on the interrelationship of German civil and corporate law, proposes a dogmatics intended for use in the development of a uniform Georgian judicial law on the issue.